Software methodologies and developers in the Mypes in Tingo María, 2017 - Yanac-Montesino, Rannoverng (2019)
The execution of the present investigation contains the systematized report on the Software Development Methodologies and the developers of the MYPES in Tingo María. Having as objective: Determine through the degree of correlation the most used methodologies by software developers for the MYPES of the city of Tingo María. The applied method had the purpose of deepening the analysis and interpretation of the results where the non-experimental design was used because it is done without deliberately manipulating variables and is based fundamentally on the observation of phenomena as they occur in their natural context to analyze them later, being the type of convenience sampling or by intentional selection, which consists of 36 graduates who are dedicated to the software development of the National Agrarian University of La Selva; where: n = 36. In order to estimate the statisticians, descriptive and inferential statistics were used and for the test of the hypothesis the correlation test was applied. With a result of 0.184, being between 0.00 and 0.19 in Spearman's Rho scale, it is concluded that the SCRUM methodology is flexible, adaptable and most of the developed ones know and use it; we arrive at these results having used the knowledge criteria that serve to evaluate methodologies since there is a moderate positive correlation between the presence and knowledge dimensions.